Adhesive Coacervates: Adhesive Coacervates Driven by Hydrogen‐Bonding Interaction (Small 43/2020). Issue 43 (27th October 2020) - Peng, Qiongyao; Chen, Jingsi; Zeng, Zicheng; Wang, Tao; Xiang, Li; Peng, Xuwen; Liu, Jifang; Zeng, Hongbo
Abstract : In article number 2004132, Hongbo Zeng and co‐workers discover a novel coacervation phenomenon by mixing silicotungstic acid and nonionic polyethylene glycol in water, driven by hydrogen bonding interactions, which provides a new platform for engineering multifunctional coacervate materials as tissue glues, wound dressings and membrane‐free cell systems.